Turn-Taking System in Institutional Context: Analysing Political Tv Interview - Nigar KH. Jooj (International Journal of Psychosocial Rehabilitation, 2019)
This study deals with how conversational turn-taking is used in British English political TV interviews in an institutional settings: An analysis of turn-taking system used in British political TV interview .This study aims at finding out to how the speakers use turn-taking in British TV interview in a political frame, primarily; (backchannel, interruption, overlap, silence, stop, intonation,), with some other turn-taking cues and gestures, How and why the British TV interviews apply those turn-taking strategies which they used?. This research works on a most prominent British politician and former UK president David Cameron who interviewed by Andrew Marr in BBC. News TV Channel. This research uses a qualitative method to analyse the interview. This research gets these results after the attention of each speaker. It is concluded that in British political TV interview; the self-selecting is prevailing, while the first-speaker selects the next speaker, and the current speaker continues technique exists. Challenging for taking the turn is apparent since more interruptions and overlaps exist in addition to the fact that the British people speak too fast. Talking at a high pitch and volume increase is dominant. However, the noteworthy thing that David Cameron uses smiles as a backchannel for respect in addition to head nodding. Finally, it very well may be said that, according to Sacks et al. (1974), the turn-taking system is violated by the members of the British political TV interview.